Application of room temperature ionic liquids as electrochemical solvents - Evans, R; Evans, Russell Griffith (2005)
﻿ This thesis is concerned with investigating the suitability of room temperature ionic liquids as solvents in which to perform voltammetry, and in characterising electrochemical processes within these media. After providing a general introduction and a background to the ionic liquid field, the results of six original studies are presented, dealing in turn with the following subjects: • The oxidation of N,N,N',N'-tetraalkyl-para-phenylenediamine (TAPD) in five ionic liquids each incorporating the bis(trifluoromethylsulfonyl)imide anion. • The reduction of oxygen in four ionic liquids based on quaternary alkyl -onium cations and heavily fluorinated anions in which the central ion is either nitrogen or phosphorous. • The simulation of double potential step chronoamperometry at a disk electrode for the case of unequal diffusion coefficients and its experimental validation using a variety of aqueous, traditional nonaqueous and ionic liquid solutions. • The rate of diffusion of N,N,N',N'-tetramethyl-para-phenylenediamme (TMPD), its radical cation and dication as a function of temperature and ionic liquid viscosity and four such solvents. • The temperature dependence of the viscosity of five ionic liquids along with the translational and rotational diffusion coefficients of dissolved 2,2,6,6- tetramethylpiperidine-N-oxyl (TEMPO). • The kinetics of the reaction between N,N-dimethyl-para-toluidine (DMT) and its electrogenerated radical cation in an ionic liquid solvent. The experimental strategy common to each report involves the application of cyclic voltammetry and chronoamperometry at disk electrodes immersed in uL-samples of ionic liquid solution. The data so measured is then analysed via the appropriate theoretical equations or, as is commonly necessary, by comparison with simulated voltammetry. Combined, these chosen redox systems provide access to information on various aspects of electrochemistry within ionic liquids, specifically (a) mass transport (b) the nature of the electron transfer process and (c) the rate of follow-up homogeneous reactions. It is the overall finding herein that while both diffusion and heterogeneous electron transfer are significantly slowed relative to the same processes in a conventional organic solvent, the rate of subsequent homogeneous chemistry remains largely unchanged.